Fields, Noblemen’s Fields, and Noblemen’s Villages of Karšuva in the 14th–18th Centuries: Sources, Statistics, Continuity, and Localization - Saviščevas, Eugenijus (Lietuvos istorijos studijos, 2022)
This paper examines the connection of pre-Christian fields with the 16th c. noblemen’s fields and the 17th–18th c. noblemen’s villages (okolica) on the basis of systematic source complexes. The sample of Karšuva district (powiat) in Samogitia was chosen for the study. After grouping the processed source material, the continuity of the names of the fields and noble villages is proven, thereby assuming the continuity of the field structure in the noble villages. After applying the mapping methodology, the geography of the noble villages and peasant villages of Karšuva is restored.
Keywords: field; noblemen’s village (okolica); Samogitia; Karšuva; registers of fireplace census; onomastics